Profitability of Manufactured Feed Pellets for Small-Scale Crop-Livestock Farmers in Tunisia - Dhehibi, Boubaker; Oussama, Jebali; Frija, Aymen; Rudiger, Udo; Ouerghemmi, Hassen; Idoudi, Zied; Rekik, Mourad; Elayed, Monia; Zaiem, Anis; Moujahed, Nizar (International Center for Agricultural Research in the Dry Areas, 2022)
The aim of this R4D Initiatives is to explore the profitability of manufactured feed pellets for small-scale crop-livestock farmers in Tunisia. During the past few growing seasons, within several R4D initiatives and projects (the SWC@Scale as part of the global GIZ ProSol Program; the CRP-Livestock “feed and forages”, and the International Fund for Agricultural Development (IFAD) funded CLCA phase 2), ICARDA and its national partners have introduced imported feed pellet machines that were donated with a 10% financial contribution (to ensure strong ownership of the technology) to some pre-selected professional farmer organizations (FO) (SMSA and GDA5) and individual farmers including agri-preneurs, with the idea of developing small feed businesses using these machines and boosting the nutrition of local herds. After assessing the available feed resources for each region (Northern, Center, and Southern), the leading members of each FO, under the supervision of the project’s scientific teams, developed various feeding formulas. Other farmers have been developing their own formulas based on consultation with local extension agents. Some of the formulas used by farmers are still under experimentation and will be the subject of this brief, aiming at validating their economic viabilities.